Effects of cancellous bone dielectric variability on microwaves detection feasibility. A simulation study - Fajardo Freites, Jesús Ernesto (2018)
The biological variability and quality of trabecular bone yield variability of its dielectric properties(permittivity and conductivity). The feasibility of detecting such differences was studied in a tomographic array of16 monopole antennas using z-polarized electromagnetic waves (OEM) at a frequency of 1.3 GHz. Finite-DifferenceTime-Domain (FDTD) simulations were performed accounting for the documented dielectric variability of cancellousbone. A sensitivity analysis method was proposed in order to identify the parameters that most affect the detection.